2004
DOI: 10.1152/ajpregu.00146.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative capacity of the dystrophic (mdx) diaphragm after induced injury

Abstract: Regenerative capacity of the dystrophic (mdx) diaphragm after induced injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 55 publications
2
27
0
4
Order By: Relevance
“…Taking into account the similarity of cell differentiation pathways during normal development and regeneration, we used immunolabeling for the following protein markers of myogenesis: (1) MyoD and myogenin, the myogenic regulatory factors expressed by committed myoblasts before and following fusion (Yablonka-Reuveni and Paterson 2001; Paoni et al 2002;Pownall et al 2002;Emerson and Hauschka 2004), (2) the embryonic isoform of myosin expressed in nascent muscle fibers (Paoni et al 2002;Matecki et al 2004), and (3) the isoform of neural cell adhesion molecule (NCAM) typical of activated myogenic cells and early myotubes (Mesires and Doumit 2002;Crameri et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the similarity of cell differentiation pathways during normal development and regeneration, we used immunolabeling for the following protein markers of myogenesis: (1) MyoD and myogenin, the myogenic regulatory factors expressed by committed myoblasts before and following fusion (Yablonka-Reuveni and Paterson 2001; Paoni et al 2002;Pownall et al 2002;Emerson and Hauschka 2004), (2) the embryonic isoform of myosin expressed in nascent muscle fibers (Paoni et al 2002;Matecki et al 2004), and (3) the isoform of neural cell adhesion molecule (NCAM) typical of activated myogenic cells and early myotubes (Mesires and Doumit 2002;Crameri et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Calpains 1 and 2 are ubiquitous non-lysosomal proteases, and are unregulated early in the time course of VIDD [6][7][8]. The calpains are involved in regulation of the cell cycle, apoptosis, and cytoskeletal reorganization, and also play roles in muscle wasting by initiating myofibrillar disassembly, which causes the myofibrillar proteins to become susceptible to further degradation by the proteasome [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The sarcolemma of normal myofibers is known to be impermeable to Procion orange, and damaged sarcolemmal fibers can be identified by their inability to exclude Procion orange from the cytoplasm [6].…”
Section: Measurement Of Sarcolemmal Injury In the Diaphragmmentioning
confidence: 99%
“…The laparoscopic procedure has been successfully used in interventions in the diaphragm 12,13 . However, until the present moment there are no studies using laparoscopic procedure for local injection in the mdx diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Matecki et al 12 , used the laparoscopy to expose the abdominal surface of the right hemidiaphragm in the mdx and wild-type (C57BL10) and induce a massive necrosis with a topical application of notexin. After surgery, the authors reported that there were no complications, confirming the mdx tolerance for this type of intervention.…”
Section: Discussionmentioning
confidence: 99%